Tinjauan Hukum Terhadap Jaminan Harta Pihak Ketiga dalam Kepailitan yang Dijadikan Harta Pailit Oleh Kurator - Safirah Maharani Putri; Muhammad Rizal Rustam (Lembaga Pengembangan Kinerja Dosen, 2025)
In bankruptcy proceedings, the presence of third parties whose assets are made part of the bankruptcy estate often leads to legal conflicts. The bankruptcy estate is a collection of assets managed by the curator to pay off the debtor's obligations to creditors. Problems arise when third-party assets, which should not be included in the bankruptcy estate, are included without a clear legal basis. This research aims to analyze the legal remedies that can be taken by third parties to protect their rights and interests. By reviewing the provisions in the Bankruptcy Law, as well as the prevailing practice, this study demonstrates the importance of verification of assets by the curator prior to inclusion in the bankruptcy estate. Legal procedures such as opposition (verzet) can be taken by third parties to challenge the curator's decision in the commercial court. The findings of this study highlight the need for a better understanding of third party rights and the legal mechanisms in place to prevent abuse of curator authority. It is hoped that this study will provide guidance to third parties in taking appropriate legal steps and strengthening legal protection in the bankruptcy process.